GE_GERICHTE C/23386/2013 vom 12. Dezember 2014 - GE Cour de justice (2014)
RELATIONS PERSONNELLES; DÉCISION DE RENVOI; OBLIGATION D'ENTRETIEN; ENFANT; MINORITÉ(ÂGE) | CC.163; CC.176.1; CC.273.1; CPC.298.1